Connectors for electronic equipment. Detail specification for 8-way, unshielded, free and fixed high density connectors for data transmission with frequencies up to 250 MHz and with current carrying capacity up to 1 A Part 02, (18th June 2020) - British Standards Institution,
No abstract available